2004
DOI: 10.1126/science.1097639
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembling Protein Microarrays

Abstract: Protein microarrays provide a powerful tool for the study of protein function. However, they are not widely used, in part because of the challenges in producing proteins to spot on the arrays. We generated protein microarrays by printing complementary DNAs onto glass slides and then translating target proteins with mammalian reticulocyte lysate. Epitope tags fused to the proteins allowed them to be immobilized in situ. This obviated the need to purify proteins, avoided protein stability problems during storage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
430
0
9

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 522 publications
(441 citation statements)
references
References 23 publications
2
430
0
9
Order By: Relevance
“…Previous NAPPA technology used an anti-GST antibody to anchor in vitro expressed C-terminal GST fusion proteins to an aminosilanized glass slide (9,10). We modified this original system by incorporating a high-affinity capture tag, the HaloTag (Promega), to immobilize nascent proteins on the array surface (18).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous NAPPA technology used an anti-GST antibody to anchor in vitro expressed C-terminal GST fusion proteins to an aminosilanized glass slide (9,10). We modified this original system by incorporating a high-affinity capture tag, the HaloTag (Promega), to immobilize nascent proteins on the array surface (18).…”
Section: Resultsmentioning
confidence: 99%
“…With conventional protein microarrays it is necessary to purify thousands of in vivo expressed proteins and to spot these purified proteins on a solid surface (5-8). In contrast, in situ synthesis protein microarray technologies simplify protein microarray fabrication by circumventing the steps of in vivo protein expression and purification (9,10,14,15). This streamlining facilitates an increase in the number of target genes that can be assayed, allowing for thousands of protein-encoding plasmids to be spotted at lower cost and in less time.…”
Section: Arabidopsis Thalianamentioning
confidence: 99%
See 1 more Smart Citation
“…Our future validation studies will focus on proteins identified in fresh experiments with the new methods of separation suggested above, since those new methods will provide more precise leads on the candidate proteins. In order to study future candidates efficiently, it may be valuable to have a high-throughput protein expression system, for example using on-chip translation of selected sequences [29]. However, immunoreactivity may only be present in proteins taken directly from cell lines or tumor tissue, so it may be necessary to use proteins purified from those materials.…”
Section: Discussionmentioning
confidence: 99%
“…In 2004 Ramachandran et al developed a method for transforming spotted DNA arrays into protein arrays, termed nucleic acid programmable protein array (NAPPA) [9,10 ]. Expression-ready biotinylated plasmid DNA is co-spotted on a glass substrate together with a biotinylated antibody.…”
Section: In Vitro Protein Synthesismentioning
confidence: 99%